O-glycan sialylation alters galectin-3 subcellular localization and decreases chemotherapy sensitivity in gastric cancer - Santos, Sofia N. (Oncotarget, 2016)
ST6GalNAc-I, the sialyltransferase responsible for sialyl-Tn (sTn) synthesis, has been previously reported to be positively associated with cancer aggressiveness. Here we describe a novel sTn-dependent mechanism for chemotherapeutic resistance. We show that sTn protects cancer cells against chemotherapeutic-induced cell death by decreasing the interaction of cell surface glycan receptors with galectin-3 and increasing its intracellular accumulation. Moreover, exogenously added galectin-3 potentiated the chemotherapeutics-induced cytotoxicity in sTn non-expressing cells, while sTn overexpressing cells were protected. We also found that the expression of sTn was associated with a reduction in galectin-3-binding sites in human gastric samples tumors. ST6GalNAc-I knockdown restored galectin-3-binding sites on the cell surface and chemotherapeutics sensibility. Our results clearly demonstrate that an interruption of O-glycans extension caused by ST6GalNAc-I enzymatic activity leads to tumor cells resistance to chemotherapeutic drugs, highlighting the need for the development of novel strategies to target galectin-3 and/or ST6GalNAc-I.